2010
DOI: 10.1183/09031936.00026410
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant protein B polymorphisms, pulmonary function and COPD in 10,231 individuals

Abstract: The surfactant protein (SP)-B gene may influence chronic obstructive pulmonary disease (COPD) and, thus, personalised medicine. We tested whether functional polymorphisms in SP-B (rs1130866 (1580T.C), rs2077079 (-18A.C) and rs3024791 (-384G.A)) associate with reduced lung function and risk of COPD in the general population.We genotyped 10,231 individuals from the general adult Danish population, and recorded spirometry and hospital admissions due to COPD. Because we previously found an association between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…Reference values for FEV 1 and FVC were internally derived for men and women separately in a subsample of healthy never-smokers using multiple regressions with age and height as covariates [12,18]. If all individuals were used as reference rather than a subsample of never-smokers, the results were similar to those presented.…”
Section: Methodssupporting
confidence: 68%
“…Reference values for FEV 1 and FVC were internally derived for men and women separately in a subsample of healthy never-smokers using multiple regressions with age and height as covariates [12,18]. If all individuals were used as reference rather than a subsample of never-smokers, the results were similar to those presented.…”
Section: Methodssupporting
confidence: 68%
“…Pulmonary surfactant-associated proteins (SP) include SP-A, SP-B, SP-C and SP-D which play pivotal roles in the function and metabolism of pulmonary surfactant. SP-B is one of the important SPs and can reduce or alter the surface tension via changing the surface area, which prevents the alveolar collapse (1)(2)(3)(4)(5). Respiratory distress syndrome (RDS) is a multifactorial and multi-gene disease, and a genetic factor has been found to be involved in the pathogenesis of RDS.…”
Section: Introductionmentioning
confidence: 99%
“…To validate our findings, we genotyped an additional 53,777 individuals from the Copenhagen General Population Study for the Thr164Ile polymorphism. These two cohorts have been successfully used in previous genetic epidemiological studies, where positive associations between variants and disease have been found [16][17][18] and in others where possible associations have been excluded [19][20][21].…”
mentioning
confidence: 99%